Lung cancer survival and deletion of GSTM1 and GSTT1 genes. A case-series from Spain. Issue 4 (July 2013) - Ruano-Ravina, Alberto; García-Basteiro, Alberto L; Pérez-Ríos, Mónica; Gómez-Mosquera, Antón; Cerdeira-Caramés, Sara; Barros-Dios, Juan Miguel
Aims and background: Lung cancer has a high incidence, and only 15% of all cases are alive 5 years after the diagnosis. Identifying the role of the genes implicated in the success of chemotherapy agents is crucial to predict survival. The objective of the study was to assess the effect of GSTM1 and GSTT1 gene deletion on lung cancer survival. Methods and study design: A consecutive sampling of lung cancer cases was performed in 1999–2000 at the University Hospital of Santiago de Compostela, Spain, and GSTM1 and GSTT1 genes were genotyped. The effect of GSTM1 and GSTT1 deletion on survival was analyzed with the logrank test and with Cox regression. Results: A total of 132 individuals were included, and more than half of them had stage IV lung cancer at diagnosis. Survival was similar irrespective of the presence or absence of the GSTM1 gene, whereas those with deleted GSTT1 had a significantly shorter survival. In multivariate Cox regression analysis, no significant effect was observed for the deletion of any of the genes, although there was a tendency towards a worse survival for those with deletion of GSTT1. The main limitation was that stage at diagnosis could not be considered in the analysis since most of the patients were diagnosed at stage IV. Conclusions: GSTT1 appears to influence lung cancer survival whereas GSTM1 seems to have no effect.